Structures hiérarchiques en terminologie - l'hyperonymie - Kacprzak, Alicja (Studia Romanica Posnaniensia, 2001)
Along with antonymy and synonymy, hyperonymy is one of the basic semantic relations in lexis. In specialistic terminologies the status of hyperonymy seems to be exceptional since this type of vocabulary reflects the hierarchic character so typical for many fields of science. This article presents the phenomenon of hyperonymy in the language of medicine in which it does not only perform the task of ordering terminology, but is also an important factor which is a condition of creation of new terms.